Identification and characterization of a novel β-lactamase gene, blaAMZ–1, from Achromobacter mucicolens - Zhang, Yuan; Zhao, Jingxuan; Zhang, Guozhi; Lin, Naru; Sha, Yuning; Lu, Junwan; Zhu, Tingting; Zhang, Xueya; Li, Qiaoling; Zhang, Hailin; Lin, Xi; Li, Kewei; et al. (Frontiers in Microbiology, 2023)
ABSTRACT Background: Achromobacter is a genus of gram-negative bacteria that can act as opportunistic pathogens. Recent studies have revealed that some species of Achromobacter show inherent resistance to β-lactams, but the resistance mechanisms of A. mucicolens have rarely been reported. Method: The bacterium was isolated using standard laboratory procedures. The agar dilution method was used to determine the minimum inhibitory concentrations (MICs). Genome sequencing was performed using the PacBio RS II and Illumina HiSeq 2500 platforms, and the Comprehensive Antibiotic Resistance Database (CARD) was used to annotate the drug resistance genes. The localization of the novel β-lactamase AMZ-1 was determined, and its characteristics were determined via molecular cloning and enzyme kinetic analysis. The phylogenetic relationship and comparative genomic analysis of the resistance gene-related sequences were also analyzed. Result: A. mucicolens Y3, isolated from a goose on a farm in Wenzhou, showed resistance to multiple antibiotics, including penicillins and cephalosporins. BlaAMZ-1 showed resistance to amoxicillin, penicillin G, ampicillin, cephalothin and cefoxitin, and the resistance activity could be inhibited by β-lactamase inhibitors. Enzyme kinetic analysis results showed that AMZ-1 has hydrolytic activity against a wide range of substrates, including cephalothin, amoxicillin, penicillin G, and cefoxitin but not ampicillin. The hydrolytic activity of AMZ-1 was greatly inhibited by avibactam but much more weakly inhibited by tazobactam. Mobile genetic elements could not be found around the blaAMZ-1-like genes, which are conserved on the chromosomes of bacteria of the genus Achromobacter. Conclusion: In this study, a novel AmpC gene, blaAMZ-1, from the animal-origin bacterium A. mucicolens Y3 was identified and characterized. It conferred resistance to some penicillins and first- and second-generation cephalosporins. The identification of this novel resistance gene will be beneficial for the selection of effective antimicrobials to treat associated infections. Keywords: blaAMZ-1, AmpC, Achromobacter mucicolens, resistance gene, kinetic analysis